Appreciation and Appreciation of Indonesian Human Identity in SMA Negeri 10 Palembang - Fadhilah, Fadhilah (Experimental Student Experiences, 2022)
This literature review aims to describe the Appreciation and Passion of Indonesian Human Identity in the School Environment. Indonesian human identity includes, diversity, Pancasila values, and religious values. The methods used are literature review, questionnaire and observation. These values that are implemented will be adjusted to the learning outcomes in schools. Then it is used to keep up with the times with various kinds of the latest issues that develop in people's lives. This will shape the character of students so that they are accustomed to facing the diversity that exists in society later. The learning process about the appreciation and passion of Indonesian Human Identity at SMA Negeri 10 Palembang is by giving symbols in the school environment and applying them, especially to Pancasila and religious values. The three Indonesian Human Identities are closely related to the learning process in accordance with the thinking of Ki Hajar Dewantara, that education must follow the nature of nature and the nature of the times for students.